Digital Domestic Violence: Are Victims of Intimate Partner Cyber Harassment - King, Ruby (Victoria University of Wellington Law Review, 2017)
The role of technology in intimate partner violence is becoming increasingly common. Intimate partner cyber harassment is a subset of "digital domestic violence", whereby partners and ex-partners use technology to stalk and harass their victims. This article examines intimate partner cyber harassment, discussing the nature of the behaviour, its prevalence in New Zealand and the damaging impact it has on its victims. The focus, however, is on New Zealand's legislative response. The conclusion reached is that despite the recent introduction of the Harmful Digital Communications Act 2015 and the review of both the Harassment Act 1997 and the Domestic Violence Act 1995, protections for victims of cyber harassment in the context of intimate partner violence remain ineffective. The current legislation fails to fully appreciate the complex issue and protections for victims lie behind procedural barriers. This article recommends that amending existing legislation is the most desirable solution as it enables pre-existing protections to be utilised to more effectively apply to and thus protect victims of intimate partner cyber harassment.